Automated generation of a model view definition from an information delivery manual using idmXSD and buildingSMART data dictionary. (October 2022) - Son, Seungwoo; Lee, Ghang; Jung, Jeaeun; Kim, Jungdae; Jeon, Kahyun
Highlights: An integrated IDM and MVD development method using bSDD as a lexicon is proposed. The method is based on three-way mapping of ISO 12006–3, ISO 16739-1, and ISO 29481-3. Particularly, it demonstrates how ISO 29481-3—a new IDM standard—can be deployed. The concept based MVD generation algorithm is used to generate a valid MVD. The method is validated against the basic FM handover MVD and the COBie MVD. Abstract: The development of an integrated information delivery manual (IDM) and model view definition (MVD) using the buildingSMART Data Dictionary (bSDD) as a lexicon has been identified as an ideal way of developing IDMs and MVDs. Several previous studies proposed methods to integrate the IDM and MVD development process. However, they were inherently limited in various ways because they were proposed before the core relevant technologies were ready. This study proposes an integrated IDM and MVD development method using bSDD as a lexicon based on three international standards—ISO 12006-3, ISO 16739-1, and ISO 29481-3. In particular, ISO 29481-3 is deployed as a core data schema to integrate the entire process. ISO 29481-3, of which the authors were the main developers, is a new ISO standard that specifies the information delivery manual XML schema definition (idmXSD). In addition, the concept-based MVD generation algorithm was adopted to generate a syntactically valid MVD. The proposed method was validated against the basic Facility Management (FM) Handover MVD and the Construction–Operations Building Information Exchange (COBie) MVD. The proposed approach is expected to help facilitate the development of IDM and MVD by allowing developers to utilize bSDD as a common lexicon and share and repurpose existing IDMs and their relationships to MVDs in a machine-readable format using idmXSD.